Brunn’s Cyst: A Rare Cause of Bladder Outlet Obstruction in a Young Man - Sailo, Stephen Lalfakzuala; Sailo, Laltanpuii (Urology Journal, 2015)
A 27-year-old man presented with obstructive voiding symptoms for eight years. He had a normal urinalysis and sterile urine culture. He had a low peak urine flow rate. Bladder ultrasound showed a 1.4 x1.2 cm cystic mass at the bladder neck and an intravenous urography revealed bilateral hydro-ureteronephrosis. On cystoscopic examination, a large cystic mass was noted at the bladder neck. Transurethral de-roofing and resection of the cystic mass was done using resection loop. The biopsy showed features of Brunn’s cyst. After the operation, the obstructive voiding symptoms subsided and he had a normal urine peak flow rate. Cystoscopy done three weeks after the operation revealed no residual lesion.